Finding Out the Visual Literacy Ability of College Level through the Analysis of Poster Design and Idea Creativity - Nadia Sigi Prameswari; Agus Cahyono; Slamet Subiyantoro; Eko Haryanto (International Conference on Science, Education, and Technology, 2022)
The challenge of education in the 21st Century is to create an education that can produce thoughtful human resources who can build social order and economy and are aware of knowledge as an individual in the 21st Century. It is crucial for learning in the present era to prioritize visual literacy skills. Visual literacy skills help the students to be capable of communicating by utilizing visual language structure until they contribute to the more global dialogue organization such as metaverse era. The purpose of this research was to review the poster design, which covers visual literacy standards and visual literacy aspects, to determine the level of students’ visual literacy skills in college. This study uses purposive sampling on visual art students from four universities. The data in this study were analyzed using interpretivism. Based on the analysis result of students’ work presentation reviewed from the visual skill. Differences in the ability to convey information, effectiveness and efficiency of images, presentation of cultural, social, and historical photos, problem-solving, and creativity. Differences in the quality of work between one individual and another related to standards in visual literacy are influenced by several aspects, namely learning experience, source of visual literacy, and sense experience.